2005
DOI: 10.1111/j.1399-3054.2005.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of silicon enhanced drought tolerance in Sorghum bicolor

Abstract: The effects of silicon application on the drought tolerance of sorghum (Sorghum bicolor (L.) Moench) were investigated for two cultivars differing in drought susceptibility. Silicon application ameliorated the decrease in dry weight under drought stress conditions, but had no effect on dry matter production under wet conditions. Under dry conditions, silicon‐applied sorghum had a lower shoot to root (S/R) ratio, indicating the facilitation of root growth and the maintenance of the photosynthetic rate and stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
312
3
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(378 citation statements)
references
References 27 publications
46
312
3
17
Order By: Relevance
“…Coffee seedlings absorbed more Si when it was added to the solution. According to Hattori et al (2005), although Si is an abundant element in nature, its availability to plants in soil solution is usually low, thus its uptake is reduced, especially for dicotyledons. However, Mitani & Ma (2005) have found increased absorption of Si in tomato plants subjected to greater concentrations of this element, which in this study was also confirmed for coffee.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee seedlings absorbed more Si when it was added to the solution. According to Hattori et al (2005), although Si is an abundant element in nature, its availability to plants in soil solution is usually low, thus its uptake is reduced, especially for dicotyledons. However, Mitani & Ma (2005) have found increased absorption of Si in tomato plants subjected to greater concentrations of this element, which in this study was also confirmed for coffee.…”
Section: Resultsmentioning
confidence: 99%
“…The leaves become more erect, favoring the incidence of light, greater CO 2 uptake and decreased excessive perspiration, allowing increased photosynthetic rate (Hattori et al, 2005;Ma & Yamaji, 2006). Other indirect effects of Si in the plant include: reduced toxic accumulation of iron and manganese and other heavy metals, like aluminum, and increased phosphorus uptake (Zhu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A aplicação de silício (Si) tem sido benéfica a diversas culturas, principalmente as consideradas acumuladoras de Si, como o arroz, cana-de-açúcar, cevada, milho, sorgo e trigo (GUNES et al, 2007;HATTORI et al, 2005;LIMA et al, 2011). Entretanto, plantas dicotiledôneas, consideradas não acumuladoras de Si, como tomate, pepino (LIANG et al, 2005), café (REIS et al, 2008), girassol (GUNES et al, 2008), feijão caupi (MALI; AERY, 2009), batata (CRUSCIOL et al, 2009;PULZ et al, 2008) e tremoço (ABDALLA, 2011) também tem respondido à aplicação de Si.…”
Section: Introductionunclassified
“…As respostas à aplicação de Si são potencializadas quando as culturas são submetidas a algum tipo de estresse (ABDALLA, 2011;GUNES et al, 2007;HATTORI et al, 2005;LIMA et al, 2011;MA, 2004). O Si tem sido associado, indiretamente, ao aumento no teor de clorofila e da capacidade fotossintética, a redução na transpiração e aumento na absorção de nutrientes (ÁVILA et al, 2010;GUNES et al, 2007).…”
Section: Introductionunclassified
“…Contributing both to plant growth and crop yield, Si helps increase the tolerance of numerous plant species to biotic and abiotic stresses (Hattori et al, 2005;Gunes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%